Challenges of Implementing an Individual Randomized Controlled Trial (Women First: Preconception Maternal Nutrition Study) in a Rural Study Site: A Case Study From Pakistan. (June 2019) - Ali, Sumera Aziz; Khan, Umber; Abrejo, Farina; Saleem, Sarah; Hambidge, Michael K; Krebs, Nancy F; Westcott, Jamie E; Goldenberg, Robert L; McClure, Elizabeth M; Pasha, Omrana
Persistent global disparities in maternal and neonatal outcomes associated with poor maternal nutrition provided the genesis of the Women First (WF) study, an individually randomized controlled trial on preconceptional maternal nutrition. This article describes the challenges that arose in implementing this trial related to nutrition or diet of the mother, in District Thatta-Pakistan. During different phases of the study, we encountered problems in identifying the eligible participants, taking consent from couples, randomizing participants in different arms, conducting biweekly follow-up visits on time, ensuring compliance to the intervention, and measuring the primary outcome within the 24 hours of birth. Each challenge was itself an opportunity for the research team to address the same through effective coordination and teamwork. Moreover, with adequate resources and dedicated staff with diverse backgrounds, it was possible to implement the WF study across the widely scattered geographic clusters of District Thatta. In addition, there are some broad strategies that could be applied to other studies such as very close contact either in person or at least by talking to mothers via phones and rapport with the study participants, the study leadership of country coordinator and the field supervisors to build trust between those on front lines and the study leadership. Moreover, continuous monitoring and supervision with frequent training and refreshers were also found to be more important to assure the data quality and to meet the study targets. Community meetings were also found to be very helpful and effective to follow the participants for a long time. Researchers conducting a similar type of studies particularly in rural areas can learn many lessons from such experiences. Thus, the process of implementing the study in one of the rural areas of Pakistan provides an insight into where and how similar individual randomized trials might be deployed.